DeepAT: A Deep Learning Wheat Phenotype Prediction Model Based on Genotype Data - Jiale Li; Zikang He; Guomin Zhou; Shen Yan; Jianhua Zhang (Agronomy)
Genomic selection serves as an effective way for crop genetic breeding, capable of significantly shortening the breeding cycle and improving the accuracy of breeding. Phenotype prediction can help identify genetic variants associated with specific phenotypes. This provides a data-driven selection criterion for genomic selection, making the selection process more efficient and targeted. Deep learning has become an important tool for phenotype prediction due to its abilities in automatic feature learning, nonlinear modeling, and high-dimensional data processing. Current deep learning models have improvements in various aspects, such as predictive performance and computation time, but they still have limitations in capturing the complex relationships between genotype and phenotype, indicating that there is still room for improvement in the accuracy of phenotype prediction. This study innovatively proposes a new method called DeepAT, which mainly includes an input layer, a data feature extraction layer, a feature relationship capture layer, and an output layer. This method can predict wheat yield based on genotype data and has innovations in the following four aspects: (1) The data feature extraction layer of DeepAT can extract representative feature vectors from high-dimensional SNP data. By introducing the ReLU activation function, it enhances the model’s ability to express nonlinear features and accelerates the model’s convergence speed; (2) DeepAT can handle high-dimensional and complex genotype data while retaining as much useful information as possible; (3) The feature relationship capture layer of DeepAT effectively captures the complex relationships between features from low-dimensional features through a self-attention mechanism; (4) Compared to traditional RNN structures, the model training process is more efficient and stable. Using a public wheat dataset from AGT, comparative experiments with three machine learning and six deep learning methods found that DeepAT exhibited better predictive performance than other methods, achieving a prediction accuracy of 99.98%, a mean squared error (MSE) of only 28.93 tones, and a Pearson correlation coefficient close to 1, with yield predicted values closely matching observed values. This method provides a new perspective for deep learning-assisted phenotype prediction and has great potential in smart breeding.